Professor János Sugár 1922-2010 - Tompa, Anna (European Journal of Oncology and Environmental Health, 2010)
His interest focused on determination of the preneoplastic processes, the reversible and irreversible phenotypic and more recently the genotypic characterization. He firstly described the electron microscopic microinvasion preceding the real invasion occurring in serious dysplastic tumors in skin, laryngeal, breast and gastroenteric pre-cancerous states (Europ J Cancer, 1968)...